Backgrounds and Consequences of the Utrecht Negotiations in Catalonia 1711-1713 - Torras i Ribé, Josep M. (Cuadernos de Historia Moderna, 2013)
This article explores the rumours and news arriving from the Utrecht negotiations between 1711 and 1713 which provoked the citizens’ disarray and inexplicable unsteadiness in the Catalan politics. Landmarks in this story were the accession of Archduke Charles to the Imperial dignity, the embarkation of the allied troops, and the negotiations in the Agreement of Hospitalet for the evacuation of the Imperial army of Catalonia, fulfilling the clauses of the Treaty of Utrecht.